2013
DOI: 10.1063/1.4804999
|View full text |Cite
|
Sign up to set email alerts
|

Water adsorption and dissociation on α-Fe2O3(0001): PBE+U calculations

Abstract: Adsorption and dissociation of water on different oxygen- and iron-terminated hematite(0001) surfaces at monolayer coverage have been studied by density-functional theory calculations, including a Hubbard-like+U correction. We considered six possible surface terminations, including four oxygen- and two iron-terminations. Binding energy of water on these terminations can be as large as 1.0 eV. On these terminations the energy barrier for the dissociation of the molecularly adsorbed water is less than 0.3 eV, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
130
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(148 citation statements)
references
References 38 publications
16
130
2
Order By: Relevance
“…The key link between the experimental and theoretical studies in the present work is a greater awareness of the complexities of the earlier stages of the oxygen-evolution reaction, as is evident from AIMD findings. The rapid room-temperature surface-hydroxylation serves as evidence for the relatively low activationenergy barriers for this process, confirming previous experimental and simulation findings [31,32,35,36]. The grey lines denote the initial configuration (before any geometry-optimisation), whilst the dotted black line is derived from the trajectory after the first picosecond (i.e., in the relatively stable post-hydroxylation structure).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The key link between the experimental and theoretical studies in the present work is a greater awareness of the complexities of the earlier stages of the oxygen-evolution reaction, as is evident from AIMD findings. The rapid room-temperature surface-hydroxylation serves as evidence for the relatively low activationenergy barriers for this process, confirming previous experimental and simulation findings [31,32,35,36]. The grey lines denote the initial configuration (before any geometry-optimisation), whilst the dotted black line is derived from the trajectory after the first picosecond (i.e., in the relatively stable post-hydroxylation structure).…”
Section: Discussionsupporting
confidence: 82%
“…Nguyen et al [36] have improved the DFT treatment of hematite-water interfaces by use of PBE+U. In many cases, very low energy barriers were found for water dissociation on hematite-001 surfaces, confirming experimental reports of widespread room-temperature dissociation of water on hematite-001 [36]; this is in some contrast to the debate as to the dominance of physical or chemical water adsorption on rutile-110 at room temperature [37][38][39]. However, to the best of our knowledge, there has been no AIMD study of the water-hematite interface, which is needed to capture the rich physic-complexity of roomtemperature chemical adsorption and the dynamical properties of the surface hematite layers, along with those of the water.…”
Section: Introductionmentioning
confidence: 99%
“…Recent PBE+U calculations [418], which considered a variety of different terminations, suggest an adsorption energy of -0.75 eV for molecular water, and -1.0 eV for the dissociated state with O water H bound to the surface Fe atom, and formation of an O surface H group (Figure 70). Dissociation is also found to be facile on a ferrylterminated surface (Figure 71), with a water molecule bound to the Fe atom of a ferryl group transferring a H atom to the ferryl oxygen.…”
Section: H 2 O/ α-Fe 2 O 3 (0001)mentioning
confidence: 99%
“…The interaction of water with α-Fe 2 O 3 (0001) surfaces has been studied both experimentally [413][414][415][416], and theoretically [416][417][418][419][420]. Kurtz and Heinrich [414] determined that water adsorbed dissociatively on an α-Fe 2 O 3 (0001) surface prepared by sputtering and 1100 K UHV annealing for pressures over 10 -5 torr, while the XPS study of Liu et al [349] suggested a threshold for hydroxylation at 10 -4 torr (both studies conducted at room temperature).…”
Section: H 2 O/ α-Fe 2 O 3 (0001)mentioning
confidence: 99%
See 1 more Smart Citation